Risk factors and preventive measures for severe orofacial and neck infections: a three-year observational study - Jarno Velhonoja; Meira Lääveri; Tero Soukka; Saara Haatainen; Noora Al-Neshawy; Ilpo Kinnunen; Heikki Irjala (BMC Oral Health)
Abstract Background The purpose of this study was to identify the risk factors of severe orofacial and neck infections and the factors that could prevent them and reduce their severity. Methods A three-year prospective observational study was conducted from 8.15.2016 to 8.31.2019 at a tertiary care hospital. 94 patients participated the study. The criteria for inclusion in the study were that the patients were adults with neck and severe orofacial infections that required treatment in hospital. Patients under the age of 18 and patients who did not consent to participate in the study were excluded. The responses to the questionnaire designed for this study were collected, as was supplemental data from medical records. The patient data were analyzed. Length of stay (LOS), intensive care unit (ICU) stay, complications and mortality were used as the main outcome variables, and various pre-admission factors and clinical and laboratory parameters were used as the predictor variables. The method used was univariate analysis. Results In 79 (84.0%) cases, surgery confirmed an abscess and pus. Age (p = 0.001) and underlying diseases (p = 0.024) contributed to complications. Bulging of the lateral pharyngeal wall or laryngeal swelling on admission was significantly related to the need for intensive care treatment (p < 0.001). The spaces most often involved were the submandibular (n = 15; 16.0%), sublingual (n = 15; 16.0%) and parapharyngeal (n = 14; 14.9%) spaces. Sixty-three cases (67.0%) were of odontogenic origin, and 58.5% of the patients reported having attended previous health care appointments due to an acute dental problem. The patients with odontogenic infections had poor oral hygiene and most likely did not brush their teeth daily (p = 0.029). “Dishwater” pus was associated with longer hospitalization (p < 0.001), intensive care treatment (p < 0.001), and surgical revisions (p < 0.001). One lethal outcome (1.1%) was reported. Conclusion Age and underlying illnesses should be considered complicating factors, and lateral pharyngeal or laryngeal edema should be considered risk factors for ICU treatment. This study also emphasized the preventive role of good dental hygiene and the importance of patients’ follow-up treatment after acute dental interventions.